Suggested activities for bacteriology analysis of selected sidewalk drinks for high school biology - Villanueva, Norma A. 1949- (1978)
This investigation endeavored to try out some activities to teach microbiological concepts to high school biology students. The activities focused on the types of bacteria present in selected sidewalk drinks. The six activities, developed and tried out, were grouped into two lessons focused on the coliform test and morphological observations of the bacteria present in the sidewalk drinks. The activities were first tried out on nine graduate students whose suggestions and comments were considered. They were again tried out to 43 second year students of Balara High School. The results were categorized into two, namely, bacteriological analysis and effectivity of the activities as teaching learning material.
Vita.
Thesis (M.A.T. Biology)--University of the Philippines, Diliman.
Keywords: Bacteria -- Philippines -- Classification; BacteriologyxStudy and teaching (Secondary) -- Philippines; Street foods -- Philippines; Beverages -- Philippines; Biology -- Experiments; Biology -- Study and teaching (Secondary) -- Philippines